North American Free Trade Agreement: an overview and description: Canada, Mexico (Government of Canada [Ottawa]CA)
Outlines the principles behind the NAFTA Agreement and provides a brief history of the negotiations. Describes Canada's objectives and how they were achieved in these negotiations. Gives a description of the proposed agreement.
Keywords: FREE TRADE AREAS